دور اليقطة الاستراتيجية في تحقيق الابداع والابتكار "دراسة ميدانية على شركة موبيليس بالوادي " - قعيد إبراهيم; مسعودي الزهرة; كوكة نور الايمان; فرحاتي فاطمة الزهرة (جامعة الوادي University of Eloued, 2024)
The study aims to identify and clarify the relationship between strategic alertness, creativity and innovation, by addressing the independent variable, which is competitive alertness, and the dependent variable, which is strategic leadership. The study used the descriptive analytical approach, by conducting a paper and electronic questionnaire directed to the employees of the Mobilis Corporation in the Valley, where it was distributed (40) questionnaires, so that (26) questionnaires were returned, of which 14 did not meet the conditions for analysis, and thus 26 questionnaires were subjected to analysis, as I relied on the (SPPS) program to extract the results. The study reached many results, the most important of which is: the existence of a positive correlation between strategic vigilance, creativity and innovation collectively and individually. It also showed that there is an impact of strategic vigilance in achieving creativity and innovation. The study recommended several recommendations, the most important of which are: creating an appropriate work environment in order to improve and develop the services provided by The institution’s employees and the establishment of a strategic vigilance cell within the institution, by providing the institution with specialized cadres in the field of using advanced software and computer hardware and granting material and moral incentives to the institution’s employees due to the efforts made by them. Which encourages them to hold periodic meetings to anticipate everything new in the internal and external work environment.
The role of the strategic plan in achieving creativity and innovation -A field study on the furniture company in El-Wadi
Keywords: يقظة استراتيجية; ابداع; ابتكار